Effect of Equisetum ramosissimum Desf. on body weight and Leptin/Ghrelin in standard and high-fat diet - Reem Issa; Mahmoud Abu Samak; Manal M. Abbas; Talal Al-Qaisi; Razan Obeidat; Bayan Ghanim; Nidal Qinna (Pensoft Publishers, 2024)
The necessity of maintaining healthy habits, diet and minimal medical complications is challenging. The current study investigates Equisetum ramosissimum on levels of leptin, ghrelin, and their ratio in association with body weight changes in animals receiving standard and high-fat diet. Ethanolic extract was prepared by maceration and total phenols and flavonoids contents were determined using Folin-cicalto and AlCl3 methods. Study animals were fed with either standard or high-fat diets prior treatment with E. ramosissimum extract (500mg/kg). Body weights were monitored and serum concentrations of leptin, ghrelin and their ratios were determined. The plant extract comprised total phenols and flavonoids of 0.03 ± 0.01 mg/mg as Gallic acid, and 0.04 ± 0.03 mg/mg as quercetin, respectively. Findings revealed significant decrease in body weights of standard-diet animals and restoration of weight to normal after treatment with extract along with significant increase in serum ghrelin concentrations with strong correlation R and R2 values in respect to body weight. As well, significant reduction in serum leptin/ghrelin ratio was positively correlated with body weight and serum leptin levels. E. ramosissimum extract possessed promising characteristics on being introduced in dietary supplements and weight control regimens. The current study presented the influence of extract in decreasing body weight in animals fed with standard diet. Moreover, it restored the weights of obese animals which received the extract after gaining weight and being on high-fat diet. Further preclinical studies are warranted to reveal the translational potentials of E. ramosissimum extract and its vital effect on adipokines.